Smoking-Related DNA Methylation is Associated with DNA Methylation Phenotypic Age Acceleration: The Veterans Affairs Normative Aging Study - Yang, Y.; Gao, X.; Just, A. C.; Colicino, E.; C. Wang; Coull, B. A.; Hou, L.; Zheng, Y.; Vokonas, P.; Schwartz, J.; Baccarelli, A. A. (Int J Environ Res Public Health, 2019)
DNA methylation may play a critical role in aging and age-related diseases. DNA methylation phenotypic age (DNAmPhenoAge) is a new aging biomarker and predictor of chronic disease risk. While smoking is a strong risk factor for chronic diseases and influences methylation, its influence on DNAmPhenoAge is unknown. We investigated associations of self-reported and epigenetic smoking indicators with DNAmPhenoAge acceleration in a longitudinal aging study in eastern Massachusetts. DNA methylation was measured in whole blood samples from multiple visits for 692 male participants in the Veterans Affairs Normative Aging Study during 1999-2013. Acceleration was defined using residuals from linear regression of the DNAmPhenoAge on the chronological age. Cumulative smoking (pack-years) was significantly associated with DNAmPhenoAge acceleration, whereas self-reported smoking status was not. We observed significant validated associations between smoking-related loci and DNAmPhenoAge acceleration for 52 CpG sites, where 18 were hypomethylated and 34 were hypermethylated, mapped to 16 genes. The AHRR gene had the most loci (N = 8) among the 16 genes. We generated a smoking aging index based on these 52 loci, which showed positive significant associations with DNAmPhenoAge acceleration. These epigenetic biomarkers may help to predict age-related risks driven by smoking.
Keywords: 80 and over Aging/*genetics Biomarkers CpG Islands *DNA Methylation Humans Longitudinal Studies Male Massachusetts Middle Aged Phenotype Self Report Tobacco Smoking/*genetics *Veterans *DNA methylation phenotypic age *aging acceleration *aging biomarker; Aged Aged